(untitled) (International Journal of Environmental Sciences, 2025)
This study investigates the correlation between youth personality characteristics and their attitudes towards the Clean India Mission (CIM), specifically analysing the presence of statistically significant relationships through Chi-square analysis. Researchers utilized non-parametric tests to better fit the categorical data structures that come from MBTI personality types, gender and Likert-type attitude responses. A primary survey with 160 young people from Salt Lake, Kolkata, was done using a structured questionnaire that asked about demographics, contained a 20-item MBTI short form, and delved into awareness and attitudes towards CIM. The data were sorted into personality types and examined with Chi-square tests of independence. The results showed that there was no statistically significant link between personality types and cleanliness attitudes, or between gender and cleanliness attitudes. These results show that personality traits may not be direct indicators of civic cleanliness views in this group. This study adds to the current conversation on how to engage people in sustainability initiatives by taking their personalities into account. It also shows that future studies need more detailed behavioural tools.